A Note on the Growth of Research in Service Operations Management - Smith, Jeffery S.; Karwan, Kirk R.; Markland, Robert E. (Production and Operations Management, 2007)
We present an empirical assessment of the productivity of individuals and institutions in terms of service operations management (SOM) research. We reviewed five mainstream operations management journals over a 17‐year time period to generate a sample of 463 articles related to service operations. The results indicate that SOM research has been growing and key contributions are being made by an array of researchers and institutions.